1976
DOI: 10.1111/j.1423-0410.1976.tb04655.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Observations on the H Antigen Sites of Human Erythrocytes Using Ferritin Antibody Conjugates

Abstract: Using immunoelectron microscopy, the distribution of the H antigen sites on human erythrocytes was observed in 40 samples of adult, newborn and fetal blood of different ABO phenotypes. The attached ferritin particles indicating the H antigen sites conspicuously varied in number from cell to cell in every specimen. The number of H antigen sites per single red cell was estimated on an average for each sample as follows: O, 3 X 10(5); B, 2 X 10(5); A1, 1.5 X 10(5); A1B, 10(5); A2B, 1.5 X 10(5); Ax, 2.5 X 10(5); A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
1

Year Published

1976
1976
1988
1988

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
2
2
1
Order By: Relevance
“…The difference in the reaction intensity among erythrocytes of blood group A is in good accordance with our previous results by transmission electron microscopy (MATSUKURA, 1972(MATSUKURA, , 1973, suggesting that the erythrocytes have different numbers of antigen sites. Further precise study will be undertaken concerning the distribution of blood group antigens of various kinds.…”
Section: Erythrocyte Samplessupporting
confidence: 92%
“…The difference in the reaction intensity among erythrocytes of blood group A is in good accordance with our previous results by transmission electron microscopy (MATSUKURA, 1972(MATSUKURA, , 1973, suggesting that the erythrocytes have different numbers of antigen sites. Further precise study will be undertaken concerning the distribution of blood group antigens of various kinds.…”
Section: Erythrocyte Samplessupporting
confidence: 92%
“…In contrast to erythrocytes from adults, the number of blood group ABH antigenic sites is substantially decreased in cord blood erythrocytes [2,10] The number of blood group antigenic sites on cord O cells reported in this com munication are in fact in good agreement with the value of 250,000 H sites per cord O cell as obtained by serum absorption meth od [5], The numbers of H sites on cord A, B and AB erythrocytes, however, reported in the same communication (150,000, 300.000 and 200,000, respectively) are con-…”
Section: Introductionsupporting
confidence: 74%
“…However, the values they obtained are far larger than those of the present study. Their values [9] for A antigen, are also greater than not only those from previous studies by this author [17,20,22], but also those reported by Kogure [15] who used the same method as theirs. On the other hand, the values for A antigen sites on red cells reported by the present author using the method of this study are similar to those of Economidou et al [4] and Cartron et al [2], who used radio iodine-labelled anti-A, and also to those of Kogure [15] [12,13].…”
Section: Discussioncontrasting
confidence: 39%
“…This fact may indicate that a few red cells in those samples used for the present study also possess the ability to bind antibody, as it was concluded that a portion of cells in the Ax samples possessed a small number of the antigen sites in the similar study for A antigen [20,22].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation